Supporting the automatic extraction of HBIM elements from point clouds - Cembranos, Javier Román; Fernández, José Llamas; Lerones, Pedro Martín; Bermejo, Jaime Gómez García; Casanova, Eduardo Zalama; Ioannides, Marinos (My University, 2018)
The purpose of this paper is just detailing a state-of-the-art procedure for the automatic recognition of specific 3D shapes from point clouds of immovable heritage assets supported on a tailored tool using PLY, PTX and PTS formats as input files. To make this tool functional and widely used, it is currently developed as a plug-in for the well-known and representative REVIT BIM software package. The procedure is particularly applied to the Castle of Torrelobatón (Valladolid, Spain) to allow the automation in cataloguing of required elements, as illustrative example of the defensive architecture from the Middle age to the Renaissance in Europe, reason why it is one of the pilot sites of the INCEPTION project. Thus the HBIM process is enhanced, which is continuing right through to provide better services to technicians, scholars and citizens.
Keywords: BIM for existing buildings; Façade parsing; HBIM; Point cloud